The alarmones (p)ppGpp are part of the heat shock response of Bacillus subtilis - Schäfer, Heinrich (PLoS Genet, 2020)
Bacillus subtilis cells are well suited to study how bacteria sense and adapt to proteotoxic stress such as heat, since temperature fluctuations are a major challenge to soil-dwelling bacteria. Here, we show that the alarmones (p)ppGpp, well known second messengers of nutrient starvation, are also involved in the heat stress response as well as the development of thermo-resistance. Upon heat-shock, intracellular levels of (p)ppGpp rise in a rapid but transient manner. The heat-induced (p)ppGpp is primarily produced by the ribosome-associated alarmone synthetase Rel, while the small alarmone synthetases RelP and RelQ seem not to be involved. Furthermore, our study shows that the generated (p)ppGpp pulse primarily acts at the level of translation, and only specific genes are regulated at the transcriptional level. These include the down-regulation of some translation-related genes and the up-regulation of hpf, encoding the ribosome-protecting hibernation-promoting factor. In addition, the alarmones appear to interact with the activity of the stress transcription factor Spx during heat stress. Taken together, our study suggests that (p)ppGpp modulates the translational capacity at elevated temperatures and thereby allows B. subtilis cells to respond to proteotoxic stress, not only by raising the cellular repair capacity, but also by decreasing translation to concurrently reduce the protein load on the cellular protein quality control system.